Representation of anti-hero in television series Breaking Bad and Weeds / Jeycobs Leroy Peter - Peter, Jeycobs Leroy (Faculty of Film, Theatre and Animation, 2015)
This dissertation explores the representation of masculine and feminine anti-heroes on television. How anti-heroes are being represented in the television series in terms of gender role? In order to conduct this research, two case studies; Breaking Bad and Weeds are chosen for analysis. These case studies are both aired on American cable television. Breaking Bad portrays a male anti-hero while Weeds centers a female anti-heroic character, thus illustrating the differences of the representation of anti-hero according to gender. Furthermore, Walter White, the central character of Breaking Bad portrays a positive masculinity while Nancy Botwin, the main character of Weeds depicts the negative femininity. Therefore, it is necessary to analyse the representation of masculinity and femininity of Breaking Bad and Weeds respectively, in accordance with the anti-hero concept. Both case studies are examined using close textual analysis, with the focus being placed on one central anti-heroic character in each case. Moreover, three episodes of each series are chosen for this research. The findings uncover that both anti-heroes are engaged in morally ambiguous activity, resulting both characters to embody problematic gender representation.